Clinical characteristics of Japanese oropharyngeal squamous cell carcinoma positive for human papillomavirus infection. (December 2014) - Nomura, Fuminori; Sugimoto, Taro; Kitagaki, Keisuke; Ito, Takashi; Kawachi, Hiroshi; Eishi, Yoshinobu; Watanabe, Ken; Igaue, Miki; Shimizu, Norio; Tomita, Makoto; Kitamura, Ken; Kishimoto, Seiji
Abstract Conclusion: Human papillomavirus (HPV)-related oropharyngeal squamous cell carcinoma (OPSCC) is considered to be a distinct entity in Japan. The combination of both HPV-DNA sequencing analysis and immunohistochemistry (IHC) for p16INK4A is useful to discriminate the OPSCC patients with a better prognosis from other cases, especially in the advanced stage. Surgical treatment is recommended for HPV-negative advanced cancer. Objective: The number of HPV-related OPSCCs has been increasing worldwide. However, the incidence and prognostic significance of this cancer in Japan have not yet been fully elucidated. Methods: Seventy-seven Japanese patients with OPSCC were enrolled in this study. The prevalence of HPV-DNA was assessed by PCR and sequencing. The expression of p16INK4A and p53 was examined by IHC. The clinicopathological parameters and disease-specific survival were analyzed for HPV-positive and -negative patients. Results: HPV-DNA was detected in 32 patients. Thirty-four patients were p16INK4A-positive by IHC. The patients who were positive for HPV infection were significantly younger. Furthermore, in the stage III or IV cases, the 3-year disease-specific survival of the HPV infection-positive group was significantly better than that of the HPV-negative group. Surgical treatment was demonstrated to lead to a good prognosis for the patients with HPV-negative advanced cancer.